Low frequency noise assessment in n- and p-channel sub-10 nm triple-gate FinFETs: Part II: Measurements and results. (February 2017) - Boudier, D.; Cretu, B.; Simoen, E.; Carin, R.; Veloso, A.; Collaert, N.; Thean, A.
Abstract: Low frequency noise measurements are used as a non-destructive diagnostic tool in order to evaluate the quality of the gate oxide and the silicon film of sub-10 nm triple-gate Silicon-on-Insulator (SOI) FinFETs. It was found that the carrier number fluctuations explain the 1/ f noise in moderate inversion for n- and p-FinFETs, which allows estimating the gate oxide trap densities. The noise spectroscopy with respect to temperature (study of the generation-recombination noise) led to the identification of the traps located in the transistors silicon film.